Spinal μ‐opioid receptor‐sensitive lower limb muscle afferents determine corticospinal responsiveness and promote central fatigue in upper limb muscle. (29th September 2014) - Sidhu, Simranjit K.; Weavil, Joshua C.; Venturelli, Massimo; Garten, Ryan S.; Rossman, Matthew J.; Richardson, Russell S.; Gmelch, Benjamin S.; Morgan, David E.; Amann, Markus
Key points: We aimed to elucidate the role of group III/IV locomotor muscle afferents in the development of central fatigue and the responsiveness of the corticospinal tract in relation to an unexercised arm muscle. Intrathecal fentanyl, a μ‐opioid receptor agonist, was employed to attenuate afferent feedback from the leg muscles during intense cycling exercise characterized by either no or severe peripheral locomotor muscle fatigue. In the absence of locomotor muscle fatigue, group III/IV‐mediated leg afferent feedback facilitates the responsiveness of the motor pathway to upper limb flexor muscles. By contrast, in the presence of leg fatigue, group III/IV locomotor muscle afferents facilitate supraspinal fatigue in a remote muscle not involved in the exercise and disfacilitate the responsiveness of associated corticospinal projections. Abstract: We investigated the influence of group III/IV lower limb muscle afferents on the development of supraspinal fatigue and the responsiveness of corticospinal projections to an arm muscle. Eight males performed constant‐load leg cycling exercise (80% peak power output) for 30 s (non‐fatiguing) and to exhaustion (∼9 min; fatiguing) both under control conditions and with lumbar intrathecal fentanyl impairing feedback from μ‐opioid receptor‐sensitive lower limb muscle afferents. Voluntary activation (VA) of elbow flexors was assessed via transcranial magnetic stimulation (TMS) during maximum voluntary contraction (MVC) and corticospinal responsiveness was monitored via TMS‐evoked potentials (MEPs) during a 25% MVC. Accompanied by a significant 5 ± 1% reduction in VA from pre‐ to post‐exercise, elbow flexor MVC progressively decreased during the fatiguing trial ( P  < 0.05). By contrast, with attenuated feedback from locomotor muscle afferents, MVC and VA remained unchanged during fatiguing exercise ( P  > 0.3). MEPs decreased by 36 ± 6% ( P  < 0.05) from the start of exercise to exhaustion under control conditions, but this reduction was prevented with fentanyl blockade. Furthermore, fentanyl blockade prevented the significant increase in elbow flexor MEP observed from rest to non‐fatiguing exercise under control conditions and resulted in a 14% lower corticospinal responsiveness during this short bout ( P  < 0.05). Taken together, in the absence of locomotor muscle fatigue, group III/IV‐mediated leg muscle afferents facilitate responsiveness of the motor pathway to upper limb flexor muscles. By contrast, in the presence of cycling‐induced leg fatigue, group III/IV locomotor muscle afferents facilitate supraspinal fatigue in remote muscle not involved in the exercise and disfacilitate, or inhibit, the responsiveness of corticospinal projections to upper limb muscles.